In-vitro screening of Kalahari browse species for rumen methane mitigation - Jacobus Johannes Francois Theart; Abubeker Hassen; Willem Adriaan van Niekerk; Belete Shenkute Gemeda (Scientia Agricola, 2015)
The nutritional value of browse foliage from the Thorny Kalahari Dune Bush veld of South Africa is not characterized. Most of this browse species is rich in tannin, but still palatable, and is consumed by ruminants during the dry season, as well as having a role to play in mitigating enteric methane emission from ruminants. In this study, the rumen methane mitigation potential of 19 browse species foliage collected from the Thorny Kalahari Dune Bush veld, was analyzed in terms of chemical composition, in vitro fermentation, digestibility and methane production. In vitro gas and methane production and organic matter digestibility (IVOMD) were determined by using rumen fluid collected, strained and anaerobically prepared. A semi-automated system was used to measure gas production (GP) from each browse species by incubating 400 mg samples in a shaking incubator at 39 °C with or without inclusion of 400 mg of polyethylene glycol (PEG). Data for all the parameters collected were statistically analyzed using the SAS (9.0) general linear model (GLM) procedure, and differences between foliage species were determined using Duncan’s multiple-range test. Acacia luederitziiand Monechma incanumshowed the best potential for decreasing methane production by up to 90 % after 48 h of incubation. The secondary components (mainly tannins) of the browse species appeared to have a significant effect on volatile fatty acids (VFA), methane and gas production as judged by the comparison of samples incubated with or without PEG inclusion. The substantial amount of crude protein (CP) content coupled with their anti-methanogenic effect during fermentation would make these browses a potential mitigation option for small scale farmers and pastoralists in sub-Sahara Africa. However, it is also very important that systematic and strategic supplementation in a mixed diet should be looked at as the way forward in terms of best utilization.